Callous‐unemotional, impulsive‐irresponsible, and grandiose‐manipulative traits: Distinct associations with heart rate, skin conductance, and startle responses to violent and erotic scenes. (7th February 2017) - Fanti, Kostas A.; Kyranides, Melina N.; Georgiou, Giorgos; Petridou, Maria; Colins, Olivier F.; Tuvblad, Catherine; Andershed, Henrik
Abstract: The present study aimed to examine whether callous‐unemotional, grandiose‐manipulative, and impulsive‐irresponsible dimensions of psychopathy are differentially related to various affective and physiological measures, assessed at baseline and in response to violent and erotic movie scenes. Data were collected from young adults ( N = 101) at differential risk for psychopathic traits. Findings from regression analyses revealed a unique predictive contribution of grandiose‐manipulative traits in particular to higher ratings of positive valence for violent scenes. Callous‐unemotional traits were uniquely associated with lower levels of sympathy toward victims and lower ratings of fear and sadness during violent scenes. All three psychopathy dimensions and the total psychopathy scale showed negative zero‐order correlations with heart rate at baseline, but regression analyses revealed that only grandiose manipulation was uniquely predictive of lower baseline heart rate. Grandiose manipulation was also significantly associated with lower baseline skin conductance. Regarding autonomic activity, findings resulted in a unique negative association between grandiose manipulation and heart rate activity in response to violent scenes. In contrast, the impulsive‐irresponsible dimension was positively related with heart rate activity to violent scenes. Finally, findings revealed that only callous‐unemotional traits were negatively associated with startle potentiation in response to violent scenes. No associations during erotic scenes were identified. These findings point to unique associations between the three assessed dimensions of psychopathy with physiological measures, indicating that grandiose manipulation is associated with hypoarousal, impulsive irresponsibility with hyperarousal, and callous‐unemotional traits with low emotional and fear responses to violent scenes.